Cloud Backup Solution - Wei Si; Feng Wang (Dianxin kexue, 2015)
As a new data backup form，cloud backup service provides users with putting the local data backup to the remote cloud.The cloud backup is being more and more focused by the industry.Combined with the demand of data backup under cloud computing environment，three aspects of“end-pipe-cloud”cloud backup solution were comprehensively analyzed，including cloud backup client，cloud backup network channel and cloud backup resource pool.In addition，according to the different business scenarios and user demand，feasible public cloud and hybrid cloud backup solutions were proposed，which could provide an important reference for the research and deployment of related field.